2019
DOI: 10.1139/cjfas-2018-0148
|View full text |Cite
|
Sign up to set email alerts
|

Predicting species distribution from fishers’ local ecological knowledge: a new alternative for data-poor management

Abstract: Many developing countries lack information to manage their endangered species, urging the need for affordable and reliable information. We used Bayesian hierarchical spatial models, with oceanographic variables, to predict the distribution range of Epinephelus marginatus, the dusky grouper, for the entire Southwest Atlantic. We ran a model using scientific information gathered from the literature and another using information gathered from fishers on species presence or absence. In both models, temperature was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Other information obtained through LEK provides insights for modeling and predicting the distributions of species. This was shown in a study by Lopes [45] for the coast of Brazil using Bayesian hierarchical spatial models and oceanographic variables, with which the author was able to predict the distribution of grouper, Epinephelus marginatus ; they used data from the literature and from fishers, and the results showed a concordance between the models that temperature predicts the distribution of this species and the reliability of the information from the fishers. Duplisea [46], studying redfish ( Sebastes spp.)…”
Section: Discussionmentioning
confidence: 77%
“…Other information obtained through LEK provides insights for modeling and predicting the distributions of species. This was shown in a study by Lopes [45] for the coast of Brazil using Bayesian hierarchical spatial models and oceanographic variables, with which the author was able to predict the distribution of grouper, Epinephelus marginatus ; they used data from the literature and from fishers, and the results showed a concordance between the models that temperature predicts the distribution of this species and the reliability of the information from the fishers. Duplisea [46], studying redfish ( Sebastes spp.)…”
Section: Discussionmentioning
confidence: 77%
“…The distribution of E. marginatus is another important concern: did the species move southwards in Brazil? The distribution of dusky grouper was shown from the south of Brazil to southern Bahia by Froese and Pauly [22] and by Lopes et al [15]; Condini et al [21] also observed one individual in this area to the south of Bahia. Data from the IUCN (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…For E. marginatus, temperatures higher than 22–23° cause anomalous eggs (Dinis et al [75], consulted October 14, 2018, at http://www.portaldoconhecimento.gov.cv/bitstream/10961/1531/1/Dinis’s%20paper.pdf). A recent study showed the importance of temperature in predicting the distribution of dusky grouper in Brazil, in addition to showing the reliability of using information from fishers to predict species distributions [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations